The "Saltin-Grimby Physical Activity Level Scale" and its application to health research - Grimby, G.; Börjesson, M.; Jonsdottir, I. H.; Schnohr, P.; Thelle, D. S.; Saltin, B. (Scandinavian journal of medicine & science in sports, 2015)
The use of a four‐level questionnaire to assess leisure time physical activity (PA) and its validation is reviewed in this paper. This questionnaire was first published in 1968 and has then been used by more than 600 000 subjects, especially in different population studies in the Nordic countries. A number of modifications to the questionnaire have been published. These are mostly minor changes, such as adding practical examples of activities to illustrate the levels of PA. Some authors have also added duration requirements that were not included for all levels of PA in the original version. The concurrent validity, with respect to aerobic capacity and movement analysis using objective measurements has been shown to be good, as has the predictive validity with respect to various risk factors for health conditions and for morbidity and mortality.